TOTAL DETERMINATION OF BACTERIA AND Escherichia coli IN THE EGGS OF ZEBRA DOVE (Geopelia striata) THAT FAILED TO HATCH IN SOME LOCAL BREEDER IN DENPASAR, BALI - Saputra, Aryadi Millenia; Kawuri, Retno; Subagio, Job Nico (SIMBIOSIS, 2022)
Birds have an attraction that has unique colors and melodious sounds, including the Zebra Dove ( Geopelia striata ). The high economic value of the Zebra Dove ( G . striata ) for the community causes excessive hunting and trading of these animals so that it can reduce bird populations in the wild. Conservation efforts are carried out to prevent the decline in bird populations in nature, namely bird breeding places. Bacterial contamination is an obstacle during the breeding process of birds. The purpose of this study was to determine the Total Plate Count (TPC) of bacteria and Escherichia coli in samples of contents and shells of Zebra Dove eggs ( G . striata ) that failed to hatch from several local bird breeders Denpasar, Bali. The research was conducted at the Microbiology Laboratory of the Biology Study Program, FMIPA Udayana University. The method used is the pour plate TPC test on Nutrient Agar (NA) and Eosin Methylene Blue Agar (EMBA) media. The results of the bacterial TPC test in the egg contents and egg shell sample obtained the highest average was found in the third breeder, while the lowest in the first breeder. Escherichia coli TPC results on the egg contents and egg shell sample obtained the highest average was found in the third breeder. The presence of the TPC of bacteria and Escherichia coli in the contents and shell samples of Zebra Dove ( G . striata ) varied every breeder.